ANALISIS PEMASARAN IKAN TUNA PADA USAHA KELOMPOK NELAYANDI DESA BAHARI KECAMATAN TOJO KABUPATEN TOJO UNA-UNA - Fitria, Fitria; Howara, Dafina (AGROTEKBIS, 2018)
Marketing Tuna fish in the village Bahari have a lot of difference between the relatively low price of the amount paid by the consumer at prices determined by the number of fishermen who certainly affect the marketing margin. Their involvement in the marketing mix to increase sales volume and marketing agencies in distributing fish species, cause marketing costs. This study aimed (1). Tuna Fish forms of marketing channels in the village of Bahari (2). Large marketing margins Tuna in the village of Bahari (3). The portion of the price received by the Tuna Fishermen in the village of Bahari (4).The level of marketing efficiency Tuna in the village of Bahari. Respondents in this study were fishermen who do production catching Tuna. Determination of the respondents conducted by using Simple Random Sampling (Simple Random Sampling). The number of respondents in this study were 30 fishermen from a total population of 100 people fishing tuna. Total population was taken from the 10 fishing groups, each group representing the three members of the fishermen. Then to respondents 5 Tuna fish traders used the assessment method (trancing method), in order to obtain each of the collectors 2 and 3 retailers. The results showed that the value of sales Tuna on Channel I that was obtained Tuna Fishermen in the village of Bahari District of Tojo Tojo Una-Una IDR.160,000,000 / kg and Channels II obtained IDR. 150,000,000 / kg Group Business Tuna Fishermen Village Maritime District of Tojo Una-Una well worth the effort, indicated by value analysis shows that the marketing channel Tuna Maritime Village District of Tojo Tojo Una-Una consists of two channels, namely: 1 . Fishermen Traders Gatherer → Collectors →Retailers→ Consumer Merchant Retailers. 2. Fishermen Traders Retailer → Consumer. Old Fish total marketing margin on first marketing channel that was IDR.10,000.00/ kg and marketing margins Tuna on a second marketing channel that wasIDR. 15,000.00/ kg. Part of the price received by fishermen on the first channel by 62% and part of the price received by fishermen on the second line by 83%.Marketing efficiency Tuna on the first channel of 12.5% and the efficiency of marketing of tuna fish on a second channel 13%. In both these marketing channels, marketing channels to II is more efficient than the first marketing channel where the efficiency of the marketing channel II is greater than I. channels Caused by comparison of total marketing costs incurred on the channel II is smaller than the channel I. In addition, the sale price received by fishermen (producer) on the second channel is greater.